The role of context in the processing of alcohol‐relevant cues - Nees, Frauke; Smolka, Michael; Flor, Herta (Addiction biology, 2012)
In line with learning theories of drug addiction, drug‐related cues may be viewed as important motivators of continued drug use. They may be differentially effective depending on the context and motivational significance. The present study aimed to test the significance of different contexts in modulating alcohol‐related cue reactivity. Pictures depicting alcohol intake or its paraphernalia and pictures without any relation to alcohol intake were varied to depict physical and social contexts or different consumptive contexts associated with full/half‐full/empty alcohol beverage containers. We obtained ratings of craving, valence and arousal of the cues as well as skin conductance responses (SCRs) and startle reflex modulation measures from 21 abstinent alcohol‐dependent patients, recruited from an addiction treatment center, and 21 matched healthy controls. Social scenes and full glasses or bottles were rated as more pleasant and arousing compared with neutral drinking situations and empty glasses or bottles in patients. Furthermore, we found a decreased startle reflex magnitude to social compared with neutral drinking situations, and both higher SCRs and decreased startle reflex magnitude to full compared with empty glasses or bottles in patients versus controls. These results show that both physical and social and consumptive contexts differentially influence cue reactivity in abstinent alcohol‐dependent patients with both social and pub‐related physical contexts, and the initial consumptive context eliciting the most appetitive and arousing responses. These data have not only important implications for our understanding of the role of learning in drug dependence but also for treatment, which needs to take these factors into account.